Time trials versus time-to-exhaustion tests: effects on critical power, W', and oxygen-uptake kinetic - Karsten, B.; Baker, J.; Naclerio, F.; Klose, A.; Bianco, A.; Nimmerichter, A. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To investigate single-day time-to-exhaustion (TTE) and time-trial (TT) -based laboratory tests values of critical power (CP), W prime (W'), and respective oxygen-uptake-kinetic responses. Methods: Twelve cyclists performed a maximal ramp test followed by 3 TTE and 3 TT efforts interspersed by 60 min recovery between efforts. Oxygen uptake (VO2) was measured during all trials. The mean response time was calculated as a description of the overall VO2-kinetic response from the onset to 2 min of exercise. Results: TTE-determined CP was 279±52 W, and TT-determined CP was 276±50 W (P=.237). Values of W' were 14.3±3.4 kJ (TTE W') and 16.5±4.2 kJ (TT W') (P=.028). While a high level of agreement (-12 to 17 W) and a low prediction error of 2.7% were established for CP, for W' limits of agreements were markedly lower (-8 to 3.7 kJ), with a prediction error of 18.8%. The mean standard error for TTE CP values was significantly higher than that for TT CP values (2.4%±1.9% vs 1.2%±0.7% W). The standard errors for TTE W' and TT W' were 11.2%±8.1% and 5.6%±3.6%, respectively. The VO2 response was significantly faster during TT (~22 s) than TTE (~28 s). Conclusions: The TT protocol with a 60-min recovery period offers a valid, time-saving, and less error-filled alternative to conventional and more recent testing methods. Results, however, cannot be transferred to W'.